Robustness Assessment of Regional GNSS Geodetic Networks for Precise Applications (Journal of Engineering, 2016)
Over the past few decades, the surveying fieldworks were usually carried out based on classical positioning methods for establishing horizontal and vertical geodetic networks. However, these conventional positioning techniques have many drawbacks such as time-consuming, too costly, and require massive effort. Thus, the Global Navigation Satellite System (GNSS) has been invented to fulfill the quickness, increase the accuracy, and overcome all the difficulties inherent in almost every surveying fieldwork. This research assesses the accuracy of local geodetic networks using different Global Navigation Satellite System (GNSS) techniques, such as Static, Precise Point Positioning, Post Processing Kinematic, Session method, and finally Real Time Kinematic for different surveying applications. To achieve this assessment, GNSS observations were executed to highlight the characteristics for each GNSS observation technique. Furthermore, the level of accuracy which is gained from each positioning technique is enormously investigated to figure out the amount of allowable error and the suitability for different geodetic applications. In relative positioning, at least two receivers (or more) are required for timing and positioning while the Precise Point Positioning necessitates single receiver. Some of geodetic applications require about positions with centimeter level of accuracy or less. The robust geodetic networks provide accurate positions which in turn serve different earth science applications.